Science Literacy in Elementary Schools: A Comparative Study of Flipped Learning and Hybrid Learning Models - Hamna Hamna; Muh. Khaerul Ummah BK (Profesi Pendidikan Dasar, 2022)
The condition of science literacy in elementary schools continues to transform using various learning technology platforms by following the dynamics of the learning conditions they face. Although previously learning interactions took place normally in the classroom, today's learning also always requires learning interactions in a virtual-based space. This study uses a comparative experimental research design Pretest-Posttest Control Group Design with a sample of 84 students from three grades who were purposively placed in two experimental class groups. Data were collected in the form of a pretest and posttest. The data analysis technique used parametric analysis in the form of the comparative Tukey test. The two models tested were proven to be effective in improving students' science literacy. The results of the comparative analysis prove that the Flipped Learning Model is more positively effective in improving students' science literacy, compared to the application of the Hybrid Learning Model. This technology-based model relies on facilities and infrastructure as a platform to support science literacy in addition to the technological capabilities of teachers and students. This study reveals the implementation of an effective learning model to be used in learning emergencies, including in normal situations after the Covid-19 pandemic